Mechanistic Insight into the Cu-Catalyzed C-S Cross-Coupling of Thioacetate with Aryl Halides. A Joint Experimental-Computational Study - Soria Castro, Silvia Mercedes (2017)
The mechanism of the Ullmann-type reaction between potassium thioacetate (KSAc) and iodobenzene (PhI) catalyzed by CuI associated with 1,10-phenanthroline (phen) as a ligand was explored experimentally and computationally. The study on C–S bond formation was investigated by UV–visible spectrophotometry, cyclic voltammetry, mass spectrometry, and products assessment from radical probes. The results indicate that under experimental conditions the catalytically active species is [Cu(phen)(SAc)] regardless of the copper source. An examination of the aryl halide activation mechanism using radical probes was undertaken. No evidence of the presence of radical species was found during the reaction process, which is consistent with an oxidative addition cross-coupling pathway. The different reaction pathways leading to the experimentally observed reaction products were studied by DFT calculation. The oxidative addition–reductive elimination mechanism via an unstable CuIII intermediate is energetically more feasible than other possible mechanisms such as single electron transfer, halogen atom transfer, and σ-bond methatesis.